Acoustic phonetics - Stevens, Kenneth N., 1924- (Cambridge, Mass. : MIT Press, 1998)
Content Description #Includes bibliographical references (p.) and index.
Preface -- 1. Anatomy and physiology of speech production -- 2. Source mechanisms -- 3. Basic acoustics of vocal tract resonators -- 4. Auditory processing of speechlike sounds -- 5. Phonological representation of utterances -- 6. Vowels : acoustic events with a relatively open vocal tract -- 7. The basic stop consonants : bursts and formant transitions -- 8. Obstruent consonants -- 9. Sonorant consonants -- 10. Some influences of context on speech sound production.
Includes bibliographical references (pages 583-602) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Phonetics, Acoustic; Phonetics; Sound; Phonetics; Acoustics; Phonétique acoustique; Phonétique.; Acoustique; phonetics; acoustics; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Phonetics & Phonology; Sound; Phonetics; Phonetics, Acoustic; Akoestische fonetiek; LINGUISTICS & LANGUAGE/General